Effective Management of Education Financing at Tahfidz Darul Hadith Palembang School Houses - Yan Syafril; Idil Saputra; Yuda Pranata; Hambali Hambali (CV. Tripe Konsultan, 2022)
This study aims to determine financing management, the existing inhibiting factors and the efforts made by Rumah Tahfidz Darul Hadits Palembang to overcome existing obstacles. This type of research is a descriptive qualitative research type with a literature study. This research was conducted at the Darul Hadith Tahfidz House in Palembang. The research subjects consisted of school principals, staff and education staff. This data collection technique was obtained from the results of observations and a summary of field notes. The analytical techniques used in this study are (1) data collection, (2) data reduction, (3) data presentation, (4) conclusion. From the results of the study, it was found that the formulation of the preparation of school financing, in this case the RAPBS, was carried out through an analysis of school operational needs, both related to the implementation of the teaching and learning process and other supports. b) The school's vision guides the preparation of the RAPBS, mission, goals and strategies, namely the principal, teachers (educators) and education staff. c) The financing of education in schools is sought by utilizing funds from local governments, foundations and the community. d) Strategies taken by schools to raise funding from the community through parents and businesses. e) The evaluation is carried out by the school regularly, every semester and academic year. f) All school personnel must provide comments and input on every program implementation and use of the school budget. g) Forms of accountability for the use of the budget carried out by the school include compiling the program's final report, which is given to all school members and their stakeholders. h) Report on the use of financing that is oriented towards accountability and transparency.